It could still be a bird - Fowler, Allan (Chicago : Childrens Press, 1990)
Identifies the characteristics of birds and provides specific examples including the penguin, ostrich, peacock, and pelican.
Includes index.
1.6
K-3
Keywords: Birds -- Juvenile literature; Birds; Birds; Birds